Findings of the Association for Computational Linguistics: ACL 2023 2023
DOI: 10.18653/v1/2023.findings-acl.691
|View full text |Cite
|
Sign up to set email alerts
|

On Text-based Personality Computing: Challenges and Future Directions

Abstract: Text-based personality computing (TPC) has gained many research interests in NLP. In this paper, we describe 15 challenges that we consider deserving the attention of the NLP research community. These challenges are organized by the following topics: personality taxonomies, measurement quality, datasets, performance evaluation, modelling choices, as well as ethics and fairness. When addressing each challenge, not only do we combine perspectives from both NLP and social sciences, but also offer concrete suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Personality detection is a complex and difficult task, since the personality traits are latent theoretical variables that cannot be directly or objectively observed (Fang et al 2023). Previous research has demonstrated a strong link between personality traits and a person's sentiments, words, and opinions (Kishima et al 2021;Johnson et al 2023).…”
Section: Generating Knowledgeable Post Augmentations From Llmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Personality detection is a complex and difficult task, since the personality traits are latent theoretical variables that cannot be directly or objectively observed (Fang et al 2023). Previous research has demonstrated a strong link between personality traits and a person's sentiments, words, and opinions (Kishima et al 2021;Johnson et al 2023).…”
Section: Generating Knowledgeable Post Augmentations From Llmsmentioning
confidence: 99%
“…Despite the ineffectiveness of LLMs in this task, previous studies have demonstrated that LLMs exhibit strong language abilities, such as text comprehension, summarization, and sentiment analysis (Zhang et al 2023;Wang et al 2023b;Hsieh et al 2023), which can be used to distill useful knowledge for enhancing small models. On the one hand, we can leverage LLMs to generate post analyses (augmentations) from the aspects of semantic, sentiment, and linguistic, which are key factors for personality detection (Fang et al 2023). In this way, we can use the augmented post information to learn better post embeddings for personality detection.…”
Section: Introductionmentioning
confidence: 99%